12 1 Geometrical Structure of M
To prove the reverse containment we assume that z is in C
N
(x
0
) ∩C
N
(x).
Then each of the vectors z − x, z − x
0
and x
0
− x is null. But z − x
0
=
(z−x)−(x
0
−x)so0=Q(z−x
0
)=Q(z−x) −2g(z−x, x
0
−x)+Q(x
0
−x)=
−2g(z −x, x
0
−x). Thus, g(z −x, x
0
−x)=0.Ifz = x we are done. If z = x,
then, since x = x
0
, we may apply Theorem 1.2.1 to the orthogonal null
vectors z − x and x
0
− x to obtain a t in R such that z − x = t(x
0
− x)and
it follows that z is in R
x
0
,x
as required.
For reasons which may not be apparent at the moment, but will become
clear shortly, a vector v in M is said to be timelike if Q(v) < 0andspacelike
if Q(v) > 0.
Exercise 1.2.4 Use an orthonormal basis for M to construct a few vectors
of each type.
If v is the displacement vector x − x
0
between two events, then, relative to
any orthonormal basis for M, Q(x − x
0
) < 0 becomes (Δx
1
)
2
+(Δx
2
)
2
+
(Δx
3
)
2
< (Δx
4
)
2
(x − x
0
is inside thenullconeatx
0
). Thus, the (squared)
spatial separation of the two events is less than the (squared) distance light
would travel during the time lapse between the events (remember that x
4
is
measured in light travel time). If x−x
0
is spacelike the inequality is reversed,
we picture x −x
0
outside the null cone at x
0
and the spatial separation of x
0
and x is so great that not even a photon travels quickly enough to experience
both events.
If {e
1
,e
2
,e
3
,e
4
} and {ˆe
1
, ˆe
2
, ˆe
3
, ˆe
4
} are two orthonormal bases for M,then
there is a unique linear transformation L : M→Msuch that L(e
a
)=ˆe
a
for
each a =1, 2, 3, 4. As we shall see, such a map “preserves the inner product
of M”, i.e., is of the following type: A linear transformation L : M→Mis
said to be an orthogonal transformation of M if g(Lx , Ly)=g(x, y) for all x
and y in M.
Exercise 1.2.5 Show that, since the inner product on M is nondegener-
ate, an orthogonal transformation is necessarily one-to-one and therefore an
isomorphism.
Lemma 1.2.3 Let L : M→Mbe a linear transformation. Then the fol-
lowing are equivalent:
(a) L is an orthogonal transformation.
(b) L preserves the quadratic form of M, i.e., Q(Lx )=Q(x) for all x in M.
(c) L carries any orthonormal basis for M onto another orthonormal basis
for M.
Exercise 1.2.6 Prove Lemma 1.2.3. Hi
nt:
To prove that (b) implies (a)
compute L(x + y) · L(x + y) − L(x − y) · L(x − y).
No
w let L : M→M be an orthogonal transformation of M and
{e
1
,e
2
,e
3
,e
4
} an orthonormal basis for M. By Lemma 1.2.3,ˆe
1
= Le
1
, ˆe
2
=
Le
2
, ˆe
3
= Le
3
and ˆe
4
= Le
4
also form an orthonormal basis for M.In